Pengaruh Pemberdayaan Perempuan Dan Pendampingan Usaha Oleh Fasilitator Pendamping Terhadap Perkembangan UMKM Pada BTPN Syariah Cabang Sidikalang - Aki Almansyah Boangmanalu; Sri Sudiarti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
MSME business actors play an important role in the Indonesian economy and have a big influence on national financial inclusion. PT. Bank BTPN Syariah Tbk is the only bank focused on empowering MSME mothers from pre-prosperous families. BTPN Syariah customers range from 18 to 60 years old who have legal types of business according to Islamic religion and state law. BTPN Syariah has an empowerment and mentoring program for MSME businesses that attracts students who are called Companion Facilitators through selection for the Merdeka Campus internship program. This assistance focuses on the needs of BTPN Syariah customers in running their business. This research aims to see and measure how effective the influence of a Facilitator's business assistance is on the development of BTPN Syariah customers' MSME businesses.